2023
DOI: 10.1101/2023.12.04.570003
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Germ granule compartments coordinate specialized small RNA production

Xiangyang Chen,
Ke Wang,
Xuezhu Feng
et al.

Abstract: Germ granules are biomolecular condensates present in most animal germ cells. One function of germ granules is to help maintain germ cell totipotency by organizing mRNA regulatory machinery, including small RNA-based gene regulatory pathways. TheC. elegansgerm granule is compartmentalized into multiple subcompartments whose biological functions are largely unknown. Here, we identify a new subcompartment of theC. elegansgerm granule, which we term the E compartment. The E compartment is nonrandomly positioned w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 93 publications
(204 reference statements)
0
6
0
Order By: Relevance
“…In C. elegans , many of the factors involved in the biogenesis of small regulatory RNAs, including siRNAs and piRNAs, as well as the Argonaute (AGO) proteins that bind these small RNAs, are largely enriched in germ granules 21 . We and other groups previously showed that the factors localized in E granules and Mutator foci contribute to the production of distinct cohorts of siRNAs using non-overlapping RNA templates 27,33,34 . piRNAs, which are 21 nt in length and start with 5′-monophosphorylated uracil, are produced from Pol II-transcribed piRNA precursors, exported to the cytoplasm, and subjected to a series of processing steps in the germline (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…In C. elegans , many of the factors involved in the biogenesis of small regulatory RNAs, including siRNAs and piRNAs, as well as the Argonaute (AGO) proteins that bind these small RNAs, are largely enriched in germ granules 21 . We and other groups previously showed that the factors localized in E granules and Mutator foci contribute to the production of distinct cohorts of siRNAs using non-overlapping RNA templates 27,33,34 . piRNAs, which are 21 nt in length and start with 5′-monophosphorylated uracil, are produced from Pol II-transcribed piRNA precursors, exported to the cytoplasm, and subjected to a series of processing steps in the germline (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…S1B), suggesting that the fluorescence-tagged proteins largely recapitulated their endogenous functions. We further collected published nematode strains expressing fluorescence-tagged perinuclear proteins, which were constructed previously in our laboratory 27,48 . In total, we collected a nematode strain library that consisted of more than 70 strains covering approximately 60 genes (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations